2010
DOI: 10.1111/j.1365-2966.2010.16956.x
|View full text |Cite
|
Sign up to set email alerts
|

Spin and structural halo properties at high redshift in a Λ cold dark matter universe

Abstract: In this paper, we examine in detail the key structural properties of high‐redshift dark matter haloes as a function of their spin parameter. We perform and analyse high‐resolution cosmological simulations of the formation of structure in a Λ cold dark matter universe. We study the mass function, shapes, density profiles and rotation curves for a large sample of dark matter haloes from z= 15 to 6. We also present detailed convergence tests for individual haloes. We find that high‐spin haloes have stronger clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 88 publications
4
17
0
Order By: Relevance
“…There are various cuts on β used in the literature to select strictly virialized haloes: Shaw et al (2006) use β > −0.2, Bett et al (2007) use |β| < 0.5 and Neto et al (2007) use β < 0.35. As noted in Davis & Natarajan (2010), we find that our haloes do not have 〈β〉≈ 0, but are offset to high values of kinetic energy such that 〈β〉 < 0 for all redshifts, and haloes are farther from virialization at higher redshifts. One possibility is that the extra terms in the virial equation ( U ext and E s ) are not negligible at higher redshifts, where large amounts of infalling material contribute to the terms.…”
Section: Simulation Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…There are various cuts on β used in the literature to select strictly virialized haloes: Shaw et al (2006) use β > −0.2, Bett et al (2007) use |β| < 0.5 and Neto et al (2007) use β < 0.35. As noted in Davis & Natarajan (2010), we find that our haloes do not have 〈β〉≈ 0, but are offset to high values of kinetic energy such that 〈β〉 < 0 for all redshifts, and haloes are farther from virialization at higher redshifts. One possibility is that the extra terms in the virial equation ( U ext and E s ) are not negligible at higher redshifts, where large amounts of infalling material contribute to the terms.…”
Section: Simulation Resultssupporting
confidence: 69%
“…Using gadget ‐2 (Springel 2005), we ran a dark matter only simulation with the WMAP 5 cosmological parameters ({Ω M , Ω Λ , Ω b , h , n , σ 8 } = {0.258, 0.742, 0.044, 0.719, 0.963, 0.796}, Dunkley et al 2009) from z ≈ 100 to z = 6 (see Davis & Natarajan 2010 for full details). Our dark matter particle mass m = 1.0 × 10 4 M ⊙ h −1 , which sets a comoving box size at 2.46 Mpc h −1 , with 512 3 dark matter particles.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that high spin halos are more clustered than low spin halos Davis & Natarajan 2010). Macciò et al (2007) on the other hand do not find any environmental dependence.…”
Section: Introductionmentioning
confidence: 95%
“…One major problem lies in their choice of initial conditions, specifically in their use of solid-body rotation. Although the total angular momentum of the gas and dark matter in their simulations is comparable that measured for minihalos in more realistic cosmological simulations (Jang-Condell & Hernquist, 2001;Davis & Natarajan, 2010), their adoption of solid-body rotation leads to the gas having an incorrect radial profile for this angular momentum. This causes the collapse of the gas to be considerably more ordered than it would be in a real minihalo, leading to the formation of an over-large disk.…”
Section: Early Studiesmentioning
confidence: 93%